Germinação e vigor de sementes de Talisia esculenta (St. Hil) Radlk em função de diferentes períodos de fermentação - Alves, Edna Ursulino; Silva, Kelina Bernardo; Goncalves, Edilma Pereira; Cardoso, Edson de Almeida; Alves, Anarlete Ursulino [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
The present study had the aim of testing the effect of different fermentation periods on the germination and vigour of pitomba seeds. The experiment was carried out in the greenhouse of the Seed Section of the Agrarian Sciences Center of the Federal University of Paraiba, Areia, PB. The fruits were picked directly from maternal trees located in the same municipal district, peeled manually and fermented for 24, 48, 72, 96 and 120 hours, in addition to seeds with pulp (without fermentation). The experiment was entirely randomized with four replications of 25 seeds per treatment. After each fermentation period, the seeds were washed in tap water and left in the laboratory environment for 24 hours on paper towels. Water content, germination and vigor (germination velocity index, seedling length and dry mass., relative frequency and medium time of germination) were measured. Less water content was shown in the seeds fermented for 96 hours (38.5%), while the largest germination percentages were observed after 76 hours of fermentation (93%). In relation to vigour, the best values occurred with 86 and 105 hours of fermentation. Fermentation is recommended for up to 105 hours as appropriate to removal of the pitomba seed aril.
Germination and vigour of Talisia esculenta (St. Hil) Radlk seeds as a function of different fermentation periods
Keywords: Pitombeira; protected environment; native fruit tree